The effect of plant distance pattern on growth and production of Abelmoschus esculentus (L.) Moench - Janan Nabilah Nur Indriana; Siti Fatimah; Sinar Suryawati (Agrovigor, 2023)
Green Okra Abelmoschus esculentus (L.) Moench is a plant  whose fruit is used as a vegetable. The content of phenolic compounds and flavonoids in okra is a natural antioxidant that is safe for the body. One way to increase okra production is to expand land by adjusting the spacing pattern. The right spacing pattern can reduce the level of competition between plants for sunlight, water, and nutrients and will reduce pests and plant disease. This study aims to obtain the right spacing pattern for maximum growth and yield of green okra plants. The research was conducted on the land owned by PT. Mitratani Dua Tujuh located in the village of wells, Ajung District, Jember Regency, using a randomizide block design with 3 replications treatment. The treathment of the spacing pattern consisted of 4 levels namely, J0 (20 cm x 40 cm x 20 cm), J1 (20 cm x 80 cm x 20 cm), J2 (15 cm x 15 cm x 80 cm x 15 cm x 15 cm) dan J3 (15 cm x 15 cm).  Observational data were analyzed using analysis of variance and further test of the sallest significant difference with a level of 5%. The results showed that the spacing pattern treatment had a significant effect on the parameters of plant height, number of stem segments,number of leaves, fruit diameter, fruit lengts,fruit weight per plant, fruit weight size S per plant, fruit production per hectare. Treatment of spacing pattern J1 (20 x 80 x 20) tended to produce fruit weight per plant and fruit production per hectare was higher than the other was treatments.